Unveiling the Immune effects of AHR in tumors: a decade of insights from bibliometric analysis (2010–2023) - Anni Xie; Ting Wang; Wenjing Shi; Fang He; Xin Sun; Ping Li (Discover Oncology)
Abstract Background The Aryl Hydrocarbon Receptor (AHR) is a transcription factor that regulates several biological processes. Its potential in anti-tumor immunotherapy is becoming clearer, yet no bibliometric studies on this topic exist. This study aims to understand the current research landscape and identify future directions through a bibliometric analysis of AHR’s anti-tumor immunological effects. Methods We conducted a comprehensive bibliometric analysis of AHR antitumor immunotherapy papers in the Web of Science Core Collection. Various aspects of the publications were analyzed, and research hotspots and future trends were identified using scientific bibliometric tools and statistical methods. Results We collected 592 English papers published between 2010 and 2023, with an almost annual increase. Most publications were from the USA, followed by China, Germany, and Italy. The journal “Frontiers in Immunology” had the most papers, and the most cited paper was Christiane A. Opitz’s “An endogenous tumour-promoting ligand of the human aryl hydrocarbon receptor.” The research is centered around AHR gene expression, with a growing focus on intestinal disease and the development of Programmed cell death ligand 1 (PD-L1) drugs. Conclusion This bibliometric study highlights the significance of AHR in immunomodulatory research, outlining the research trends and key contributors. It suggests AHR’s immune effects may mediate the process of colitis cancer transformation, providing valuable insights for future anti-tumor immunotherapy strategies based on AHR.